Degradation Kinetics of Bioactive Compounds and Antioxidant Activity of Pomegranate Arils during the Drying Process - Baslar, Mehmet; Karasu, Salih; Kilicli, Mahmut; Us, Ahmet Abdullah; Sagdic, Osman (WALTER DE GRUYTER GMBH, 2014)
In this study, the drying kinetics of pomegranate arils, the degradation kinetics of some bioactive compounds, and changes in color values during the drying process were investigated. The drying process was performed by a forced air circulating oven at 55, 65, and 75 degrees C. Drying times were calculated to be 1,020, 520, and 330 min, respectively. Effective moisture diffusivity values ranged from 5.39 x 10(-11) to 1.70 x 10(-10) m(2) s(-1) and increased with increases in temperature. Six different thin-layer drying models were applied to evaluate the goodness of the model. The degradation rate of bioactive compounds increased at higher temperatures; however, remaining amounts of phenolic, anthocyanin, and flavonoid compounds after drying were higher in samples dried at 75 degrees C. The highest antioxidant capacity value was observed in the pomegranate arils dried at 75 degrees C. While the L* values of pomegranate arils decreased after the drying process, the a* values increased.
Keywords: pomegranate; phenolic compounds; antioxidant; drying kinetics; moisture diffusivity; PHENOLIC-COMPOUNDS; VACUUM; COLOR; CAPACITY; TEMPERATURE; MODELS; PEEL; Food Science & Technology